Epidemiological and clinical characteristics of patients with malaria admitted to a hospital in Mérida, Venezuela. (5th December 2019) - Gabaldón-Figueira, Juan C; Salmen, Siham; Silva, Nubia; Mancilla, Betania; Vielma, Silvana
Abstract: Background: Malaria is expanding rapidly across Venezuela, spreading outwards from traditional high transmission regions in the southeast of the country, but the lack of official data make it impossible to understand the reasons for this expansion and to estimate its real magnitude. This study aims to evaluate the epidemiological characteristics driving the re-emergence of malaria in Mérida, a state in the west of Venezuela, where no cases have been reported since 2003, and also to study the clinical presentation of the disease in patients presenting with malaria. Methods: Thirty-three patients who presented with anemia and fever and with a microscopic diagnosis of malaria were examined and interviewed. Data were collected in standardized forms and analyzed. One-way analysis of variance was used to study differences among patients infected with different parasites. Results: Twenty-two patients were from the Zulia state and eleven were from the Mérida state, mainly from the lowlands south of Lake Maracaibo. Six of these patients traveled to the Bolívar state between 2017 and 2019. Thirteen patients presented with the WHO criteria for severe malaria. Conclusions: Domestic migration to the southeast of Venezuela may have played an important role in the expansion of malaria in previously existing endemic areas of transmission and also in the increase in the number of cases of severe malaria.